Patient, Client, Homo Consultans ? an Andragogic Perspective - Kargulowa, Alicja (INSTED: Interdisciplinary Studies in Education & Society, 2017)
This article contains the names of people who use counsellors? help. They have typological value, not only specifying the variety of the contemporary ?counsellees?, but they also indicate economic, social and cultural changes, which appeared in the last century, shaping the relation of people towards the surrounding world, other people and themselves. They indicate changes in the counselling understood as an interpersonal relation, organised activity and the process of social life ? the places where adults learn.